2013
DOI: 10.4330/wjc.v5.i11.404
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation in spontaneously hypertensive rats: Advantages and limitations for human applications

Abstract: Taurine (2-aminoethanesulfonic acid) is a β-amino acid found in many tissues particularly brain, myocardium, and kidney. It plays several physiological roles including cardiac contraction, antioxidation, and blunting of hypertension. Though several lines of evidence indicate that dietary taurine can reduce hypertension in humans and in animal models, evidence that taurine supplementation reduces hypertension in humans has not been conclusive. One reason for the inconclusive nature of past studies may be that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This study also found a decrease in the percent of 1-h SBP increase, which has not been reported previously. However, the taurin content may explain this finding, because it caused a decrease of BP in a previous study [46]. Several studies have shown that energy drinks exerted different effects on BP, but the use of different volumes and the concentration of components [16,21] or the fact that the beverages tested were prepared using only some of the components of the commercial brands [22] may be the reasons for this disagreement.…”
Section: Discussionmentioning
confidence: 86%
“…This study also found a decrease in the percent of 1-h SBP increase, which has not been reported previously. However, the taurin content may explain this finding, because it caused a decrease of BP in a previous study [46]. Several studies have shown that energy drinks exerted different effects on BP, but the use of different volumes and the concentration of components [16,21] or the fact that the beverages tested were prepared using only some of the components of the commercial brands [22] may be the reasons for this disagreement.…”
Section: Discussionmentioning
confidence: 86%
“…Over 50 percent of the total free amino acid pool in the heart is reportedly occupied by taurine ( 125 ), which appears to have a positive inotropic action on cardiac tissue ( 126 ) and to lower high blood pressure ( 127 , 128 ). Taurine protects cardiomyocytes from damage mediated by either excessive or inadequate calcium ion levels due to its regulatory effect on the activity of the voltage-dependent calcium and sodium channels ( 129 ).…”
Section: The Anti-oxidant Efficacy Of Taurine Against Cardiac- Associated Oxidative Stressmentioning
confidence: 99%
“…Although perinatal taurine supplementation does not induce salt-sensitive hypertension, taurine supplementation in late pregnant rats stimulates postnatal growth and induces obesity and insulin resistance in adult offspring (Hultman et al 2007). Moreover, in adult SHR, taurine supplementation accelerates the hypertensive response to a high salt diet during nighttime but not daytime (Suwanich et al 2013). …”
Section: 4 Discussionmentioning
confidence: 99%